Factors associated with level of satisfaction in nursing care among cancer patients at teaching hospitals of Tehran City, Islamic Republic of Iran - Akhtari Zavare, Mehrnoosh; Abdullah, Mohd Yunus; Syed Hassan, Syed Tajuddin; Md Said, Salmiah; Kamali, Mohammad (Faculty of Medicine and Health Sciences, University Putra Malaysia, 2010)
Background: Patients' satisfaction with their nursing care is an important issue in assessing the quality of nursing care. In Iran, cancer patients' satisfaction at teaching hospitals of Tehran City has not been investigated. Aim: A cross sectional study was conducted to determine the level and identify factors that contributed to patients' satisfaction in nursing care provided at selected teaching hospitals in Tehran City, Islamic Republic of Iran. Method: A proportional stratified sampling method was used and data were collected via face-to-face interview based on a validated Patient Satisfaction Questionnaire (PSQ). A total of 384 cancer patients aged 14 years and above were selected. Result: The majority of respondents were males (201, 52.4%), age group 45-54 years (102, 26.4%); employed (202, 52.6%) and with a family monthly income of US$200-500 (234, 60.9%).The majority (314, 81.8%) of respondents were hospitalized between 2 to 5 days, and most (204, 54.0%) of them were admitted to teaching hospital B of The University of Medical Science.' A majority of the respondents (318, 82.8%) was satisfied with the nursing care provided, while the others (66, 17.2%) were not. Generally, most of the respondents were satisfied with the amount of information given by the nurses (294, 76.6%), technical quality (295, 76.8%), interpersonal relationship (371, 96.6%), and physical environment (267, 69.5%). There was a positive significant relationship between patients' satisfaction and type of hospital (y2=4.985; df=1; p=O.O26, n=384). Using the University's hospital type was found to be the best predictor for level of satisfaction. Conclusion: Most of the respondents were satisfied with the nursing care. However, the respondents suggested several improvements such as increasing the number of doctors, improving socio environment factors in terms of privacy and interpersonal relationship, and improving on the existing facilities. Further research is needed to study in depth the socio-cultural and environment parameters which are relevant to patients' satisfaction with nursing care.